Systematic review on the efficacy and safety of ixabepilone-based chemotherapy regimen in triple-negative breast cancer - Azizah, Maghfira Rahma; Hanum, Halida Adib; Norahmawati, Eviana; Fakurazi, Sharida; Kawamoto, Yoshiyuki; Permana, Sofy; Widodo, Edwin; Endharti, Agustina Tri (Academic Association of Pharmaceutical Sciences from Antofagasta, 2024)
Context: Triple-negative breast cancer (TNBC) has poor prognosis, high mortality, and recurrence rates. Ixabepilone or ixempra could be a promising agent for TNBC, especially in the taxane-and/or anthracycline-resistant population. Aims: To evaluate the efficacy and safety of ixabepilone-based chemotherapy compared to ixabepilone-free chemotherapy in TNBC patients. Methods: This review followed the preferred reporting items for systematic reviews and meta-analysis guidelines. The eligibility criteria included randomized control trials (RCTs) in 2013-2023 comparing ixabepilone-based with ixabepilone-free chemotherapy regimen in TNBC. Results: This study identified four eligible RCTs. One study showed that patients treated with ixabepilone had a significant improvement in disease-free survival, had a better response, and a lower risk of disease recurrence compared to those treated with taxane-based regimen. However, two studies showed no differences in terms of overall survival (OS), disease-free survival, and pathological complete responses rates in both treatment arms. Ixabepilone addition to capecitabine significantly prolonged progression-free survival and objective response rate in TNBC patients, but did not significantly improve OS (n= 1). Conclusions: The effectiveness and safety of ixabepilone-based chemotherapy versus ixabepilone-free treatment for triple-negative breast cancer (TNBC) patients vary among studies. More research is needed to better understand the effectiveness and safety of ixabepilone-based chemotherapy versus ixabepilone-free treatment in TNBC patients.